Pengaruh Pandemi COVID-19 terhadap Kelompok Masyarakat Ekonomi Kelas Bawah - Abd. Hafid (STAI DDI Kota Makassar, 2020)
The economic cycle plummeted because of the C-19 pandemic outbreak, how then the working class people who are required to maintain health and break the chain of C-19 development at the same time are forced to work to continue their survival. How many workers because of this epidemic they are infected and then laid off, the pattern of social inequality is very clear in social life, where workers who are actually in the lower class category must continue to do work directly while the elites work in a relaxed and safe manner from their homes (WFH). Every day cases of C-19 infection increase the government's policy regarding large-scale social restrictions (PSBB) is considered very ineffective because it cannot answer the confusion caused by this system in other fields.) Things like this then contract the thinking of the working class to resist by not believing or not being afraid of the C-19 epidemic on the pretext of religion